Anatomical texture patterns identify cerebellar distinctions between essential tremor and Parkinson's disease. Issue 8 (23rd March 2021) - Hett, Kilian; Lyu, Ilwoo; Trujillo, Paula; Lopez, Alexander M.; Aumann, Megan; Larson, Kathleen E.; Hedera, Peter; Dawant, Benoit; Landman, Bennett A.; Claassen, Daniel O.; Oguz, Ipek
Abstract: Voxel‐based morphometry is an established technique to study focal structural brain differences in neurologic disease. More recently, texture‐based analysis methods have enabled a pattern‐based assessment of group differences, at the patch level rather than at the voxel level, allowing a more sensitive localization of structural differences between patient populations. In this study, we propose a texture‐based approach to identify structural differences between the cerebellum of patients with Parkinson's disease ( n = 280) and essential tremor ( n = 109). We analyzed anatomical differences of the cerebellum among patients using two features: T1‐weighted MRI intensity, and a texture‐based similarity feature. Our results show anatomical differences between groups that are localized to the inferior part of the cerebellar cortex. Both the T1‐weighted intensity and texture showed differences in lobules VIII and IX, vermis VIII and IX, and middle peduncle, but the texture analysis revealed additional differences in the dentate nucleus, lobules VI and VII, vermis VI and VII. This comparison emphasizes how T1‐weighted intensity and texture‐based methods can provide a complementary anatomical structure analysis. While texture‐based similarity shows high sensitivity for gray matter differences, T1‐weighted intensity shows sensitivity for the detection of white matter differences. Abstract : In this study, we analyzed anatomical differences of the cerebellum among patients using two features: T1‐weighted MRI intensity, and a texture‐based similarity feature. Our results show anatomical differences between groups that are localized to the inferior part of the cerebellar cortex. Both the T1‐weighted intensity and texture showed differences in lobules VIII and IX, vermis VIII and IX, and middle peduncle, but the texture analysis revealed additional differences in the dentate nucleus, lobules VI and VII, vermis VI and VII. This comparison emphasizes how T1‐weighted intensity and texture‐based methods can provide a complementary anatomical structure analysis. While texture‐based similarity shows high sensitivity for gray matter differences, T1‐weighted intensity shows sensitivity for the detection of white matter differences.